14:E Konstmässan Stockholm Art Fair 1994 : Tabula Rasa. (Stockholm : Stockholm Art Fair, 1994)
Alechinsky, Pierre ; Andre, Carl ; Balka, M. ; Bonde ; Chia ; Dine ; Falk, J. ; Fontana, L. ; Flanagan, Barry ; Hagström, A. ; Holstein, B. ; Kantor ; Kiefer, A. ; Kirkeby, Per ; Matta ; Nilsson, A. ; Panamarenko ; etc.
14:E Konstmässan Stockholm Art Fair 1994 / 14th Art Fair, Stockholm 1994, Stockholm, 9-14 mars 1994
kunstcatalogus